Gesture sonification for enhancing agency: an exploratory study on healthy participants - Felix Schoeller; Felix Schoeller; Parham Ashur; Joseph Larralde; Clement Le Couedic; Rajeev Mylapalli; Karthikeyan Krishnanandan; Anna Ciaunica; Anna Ciaunica; Adam Linson; Mark Miller; Nicco Reggente; et al. (Frontiers in Psychology, 2025)
BackgroundBody awareness (BA) and proprioception, which are essential components of the sense of agency (SA), are often altered in various mental disorders such as posttraumatic stress disorder (PTSD). However, the relationship between BA, proprioception, and SA, as well as the methods to manipulate them, remain unclear. This study explored using real-time gesture sonification (GS), i.e., wearable technology transforming body movements into sounds, to enhance proprioception, BA, and thus the SA.MethodsIn this within-subjects design, 17 healthy adults (mean age = 25.5 years) with varying dance expertise (novice, amateur, expert) improvised movements to match sounds with and without auditory feedback from motion sensors on wrists/ankles modulated by their gestures. BA, immersion, pleasure, and self-efficacy were measured.ResultsSonification significantly increased body awareness, reward, and immersion (all p < 0.05).ConclusionGS can enhance BA and the SA, pleasure, and control during physical activity. This highlights potential mental health applications, such as agency-based therapies for PTSD. Manipulating bodily perception could improve symptoms and embodiment. Further research should replicate this in clinical populations and explore neurocognitive mechanisms.